Factors affecting oral frailty and nutritional status in older adults living alone - Cha, Ji-Min; Jung, Dong Hoon; Kim, Ha-neul; Lim, Hee-Sook (Frontiers in Nutrition, 2025)
IntroductionThe global aging population is rapidly increasing, with South Korea experiencing the fastest aging rate among the OECD countries. Consequently, the number of older adults living alone is sharply increasing, creating an urgent social issue that necessitates comprehensive and systematic care service policies. Frailty is a key indicator of the overall health status of older adults, and because oral health and nutrition are closely linked, continuous monitoring is essential in this population.MethodsThis study aimed to analyze the factors influencing oral frailty and nutritional status among older adults living alone in South Korea by using an oral frailty screening tool, which is one of the recently developed function-specific frailty screening tools. A survey of 606 adults aged 65 years and older examined their sociodemographic characteristics, health status, oral health, and nutritional status. Logistic regression analysis identified key factors affecting oral frailty and nutritional status.ResultsResults revealed a direct association between oral frailty and nutritional status, with loneliness emerging as a common factor influencing both variables.DiscussionThese findings highlight the importance of maintaining a balanced diet alongside proper oral hygiene and emphasize the need for integrated interventions including emotional support. Therefore, this study underscores the need for continuous care strategies to promote healthy aging and improve the quality of life of older adults.